Pengaruh Media Poster Digital terhadap Kemampuan Menulis Teks Persuasi Siswa Kelas VIII SMP PGRI 1 Depok - Linansera, Angelina; Ade Siti Haryanti; Adi Permana (PT. Impola Toba Lendt, 2025)
The purpose of this study was to determine the effect of digital poster media on the ability to write persuasive texts. Media on the ability to write persuasive texts of grade VIII students of SMP PGRI 1 Depok. PGRI 1 Depok. Method The quantitative research method used is the experimental method. The researcher used a Quasi Experimenta Design which more precisely uses Post-Test Only Control Group. In this research design there are experimental groups and control group. The experimental group received treatment, while control group does not. The average ability to write persuasive text with using digital poster learning media got a score of 83 which means higher than the conventional learning media (picture) which got an average value of 66.5, besides that, the average value of the ability to write persuasive text of the experimental class using digital poster learning media can exceed the Minimum Completeness Criteria (KKM) given by SMP SMP. (KKM) given by SMP PGRI 1 Depok, which is 79 > 67. The positive effect is shown by the results of the t test where thitung = 13.58 47 while ttbael = 1.6722 so that thitung > ttbael.